Cover Feature: Mechanism of Mechanochemical C−H Bond Activation in an Azobenzene Substrate by PdII Catalysts (Chem. Eur. J. 42/2018). Issue 42 (16th July 2018) - Bjelopetrović, Alen; Lukin, Stipe; Halasz, Ivan; Užarević, Krunoslav; Đilović, Ivica; Barišić, Dajana; Budimir, Ana; Juribašić Kulcsár, Marina; Ćurić, Manda
Abstract : A comparative mechanistic study of the mechanochemical C−H bond activation in an unsymmetrical azobenzene by common Pd(II) catalysts is reported, using liquid and/or solid additives. The C−H bond activation was achieved by all used Pd(II) precursors and their reactivity increases in the order [Pd(OAc)2 ]3 2 (MeCN)2 2 <[Pd(MeCN)4 ][BF4 ]2 . In situ and ex situ spectroscopic monitoring of these reactions enabled a detailed insight into their mechanism and kinetics. More information can be found in the Full Paper by M. Ćurić, M. Juribašić Kulcsár, et al. onpage 10672 .